Distinct Roles of Cellular Lck and p80 Proteins in Herpesvirus Saimiri Tip Function on Lipid Rafts - Park, Junsoo (American Society for Microbiology, 2003)
Lipid rafts are proposed to function as platforms for both receptor signaling and trafficking. Following interaction with antigenic peptides, the T-cell receptor (TCR) rapidly translocates to lipid rafts, where it transmits signals and subsequently undergoes endocytosis. The Tip protein of herpesvirus saimiri (HVS), which is a T-lymphotropic tumor virus, interacts with cellular Lck tyrosine kinase and p80, a WD domain-containing endosomal protein. Interaction of Tip with p80 induces enlarged vesicles and recruits Lck and TCR complex into these vesicles for trafficking. We report here that Tip is constitutively present in lipid rafts and that Tip interaction with p80 but not with Lck is necessary for its efficient localization in lipid rafts. The Tip-Lck interaction was required for recruitment of the TCR complex to lipid rafts, and the Tip-p80 interaction was critical for the aggregation and internalization of lipid rafts. These results suggest the potential mechanism for Tip-mediated TCR downregulation: Tip interacts with Lck to recruit TCR complex to lipid rafts, and it subsequently interacts with p80 to initiate the aggregation and internalization of the lipid raft domain and thereby downregulate the TCR complex. Thus, the signaling and targeting functions of HVS Tip rely on two functionally and genetically separable mechanisms that independently target cellular Lck tyrosine kinase and p80 endosomal protein.